Economic impact of ischemic heart diseases in Brazil: comparison through the input-output matrix to the years 2006 and 2014 - Cezar, Henry Ledur Paz; Montibeler, Everlam Elias; Cordeiro, Daniel Rodrigues (Gestão & Regionalidade, 2021)
The purpose of the article was to measure the impacts caused by Ischemic Heart Diseases (IHD) on Brazilian GDP in 2006 and 2014. The effects of IHD were assessed by applying shocks applied to 56 sectors, in current values of the impact on income. The method used included information on the Disability Adjusted Life Years (DALY), developed by the World Health Organization (WHO) through the study of Global Illness Burden; and Leontief Inverse. The results showed that the direct impacts of the IHD on GDP in 2006 were approximately US$ 166 million and US$ 362 million in 2014, and direct and indirect impacts were US$ 800 million in 2006 and US$ 1.3 billion in 2014. The total economic impact exceeded those of US$ 919 million in 2006 and US$ 1.7 billion in 2014.